COMPARION OF DEPTH OF CURVE OF SPEE IN CLASS I, II AND III MALOCCLUSIONS - Sadia Naureen; Col Hameed Ullah Jan (R); Huma Ghazanfar Kiani; Tariq Hameed; Capt Umer Hameed (Pakistan Oral & Dental Journal, 2020)
Curve of spee is a normal occlusal curve which helps in mastication and normal occlusal function. The objective of this study was to compare the depth of curve of Spee in class I, II, and III malocclusions.This study was conducted at the department of Orthodontics, Rawal Institute of Health Sciences (RIHS) Islamabad from January 2017 to July 2017 on 300 participants. It was a retrospective comparative study. One hundred patients from each class of malocclusions (I, II and III) were selected with the age 11-35 years by non-probability consecutive sampling technique. Lower arch impressions and depth of curve of Spee (COS) was taken on the study casts in each of the malocclusion group. Data was analyzed using SPSS 20.0. Analysis of variance (ANOVA) was applied to compare the depth of COS among three classes of malocclusion setting p-value < 0.05 to be of significance.The total participants were 300 in which 141(47%) were males and 159(53%) were females. The mean age was 17.92±4.98 years. The mean value for COS was 3.146±3.403 mm. The mean COS was highest in class I (3.32±1.33mm) followed by class III (2.63± 0. 576 mm) and least was in class II (2.54±1.205mm). The difference was statistically significant (P
Keywords: Curve of Spee COS; malocclusion; orthodontics; class of malocclusion